Portuguese consumer exposure to cosmetic products: risk assessment of ingredients in facial and body moisturizers - Rodrigues, Matilde (2019)
The cosmetic industry launches thousands of products annually. Most chemicals are added to the cosmetic product in the form of preservatives and fragrances and some are classified as toxic and prohibited from being used as ingredients because they can cause cancer diseases, mutations, reproductive toxicity, and endocrine disruption.